Review of Loukianos Hassiotis, “Γεια σας, εγγλεζάκια!” Βρετανοί στρατιώτες στην Ελλάδα (1941–1945) [Welcome, English lads! British soldiers in Greece, 1941–1945] - Syriatou, Athena (Historein, 2024)
Review of Loukianos Hassiotis, “Γεια σας, εγγλεζάκια!” Βρετανοί στρατιώτες στην Ελλάδα (1941–1945) [Welcome, English lads! British soldiers in Greece, 1941–1945]. Athens: Metaixmio, 2019. 392 pp.